Single-cell RNA sequencing of tumor-infiltrating NK cells reveals that inhibition of transcription factor HIF-1α unleashes NK cell activity - Ni, Jing; Wang, Xi; Stojanovic, Ana; Zhang, Qin; Wincher, Marian; Bühler, Lea; Arnold, Annette; Correia, Margareta; Winkler, Manuel; Reiners-Koch, Philipp-Sebastian; Sexl, Veronika; Höfer, Thomas; et al. (Immunity, 2020)
Enhancing immune cell functions in tumors remains a major challenge in cancer immunotherapy. Hypoxia is a common feature of solid tumors, and cells adapt by upregulating the transcription factor HIF-1α. Here, we defined the transcriptional landscape of mouse tumor-infiltrating natural killer (NK) cells by using single-cell RNA sequencing. Conditional deletion of Hif1a in NK cells resulted in reduced tumor growth, elevated expression of activation markers, effector molecules, and an enriched NF-κB pathway in tumor-infiltrating NK cells. Interleukin-18 (IL-18) from myeloid cells was required for NF-κB activation and the enhanced anti-tumor activity of Hif1a−/− NK cells. Extended culture with an HIF-1α inhibitor increased human NK cell responses. Low HIF1A expression was associated with high expression of IFNG in human tumor-infiltrating NK cells, and an enriched NK-IL18-IFNG signature in solid tumors correlated with increased overall patient survival. Thus, inhibition of HIF-1α unleashes NK cell anti-tumor activity and could be exploited for cancer therapy.
Gesehen am 27.10.2020